Trade unions futures: organization and future dynamics - Almeida, P. P. (2018)
Trade Unions Futures depicts a synthesis of trends in a globalized context for Trade Unions, considering that this context is changing. The challenges that the Unions and face are manifold. In Trade Unions Futures we turn our attention to three aspects that we consider essential for the understanding of these changes, namely: new social movements and government; forms of differentiated regulation; and new challenges for trade union communication and the Web. Main results pertaining to new forms of unionism and the workers’ expectations will also be put forward.